PENGARUH PENERAPAN UNDANG-UNDANG PROFESI AKUNTAN PUBLIK TERHADAP MINAT MAHASISWA MENJADI AKUNTAN PUBLIK (STUDI KASUS DI UNIVERSITAS INDONESIA DAN UNIVERSITAS TRISAKTI) - Mulyaningsih, May (Universitas Pakuan, 2016)
This research examines perception and motivation on public accountant influenced the interest of S1 Accounting students toward the profession in Indonesia due to Act No. 5 Year 2011 about Public Accountant. Population in this research are S1 Accounting students who are taking Auditing II subject in University of Indonesia (245 students) as representative of state university and Trisakti University (426 students) as representative of private university in Indonesia. Total sample students per university determined by using Slovin Formula with 5% significant (error) level. Qualitatif data type that used in this research is primary data which is collected using survey method by distributing the quesioner. Independent variables (perception and motivation) also dependent variabel (interest) which are interval scale are measured using Likert scale. The validity test with product moment correlation formula and the realibility test with Spearman Brown formula are used for examining data quality. The classic assumption tests which are consist of normality test, multicolinearity test, autocorrelation test and heteroscedastisity test are used for testing all hypothesis. Hypothesis also tested by using regression with double regression analysis equation. Results show that perception and motivation on public accountant, simultaneously and partially, influenced the interest of S1Â Accounting students in University of Indonesia and Trisakti University toward public accountant.Â Keywords: Perception, Motivation, Interest, Public Accountant, Act No. 5 Year 2011 about Public Accountant